Steady-state and time-resolved luminescence in InGaN layers - Seitz, R.
InGaN layers are used as active layers of high brightness in nitride-based LEDs and lasers. Despite the progress in device development many of the fundamental optical properties are not completely understood. InGaN samples with different In content are studied by steady-state and time-resolved photoluminescence. The low-temperature photoluminescence spectra show a near band edge emission that shifts to lower energies with increasing In content, excitation wavelength and delay times. The emission is broader than typical excitonic emission from binary material. Temperature dependent measurements indicate that the near band edge emission is an overlap of various emission bands with different quenching behaviour.